Protection induced in BALB/c mice by the high-molecular-mass (hMM) fraction of Paracoccidioides brasiliensis - Pavanelli, Wander R.; Kaminami, Mari S.; Geres, Juliana R.; Sano, Ayako; Ono, Mario A.; Camargo, Isabel Cristina Cherici [UNESP]; Itano, Eiko N. (Springer, 2007)
Paracoccidioidomycosis (PCM) is a granulomatous disease caused by a dimorphic fungus, Paracoccidioides brasiliensis. The present study investigated the protective activity of the P. brasiliensis high-molecular-mass (hMM) fraction (similar to 380 kDa) in experimental murine PCM. In the first step, lymphocyte proliferation and production of IFN gamma (but not IL-4) were observed in in vitro spleen cells (from female BALB/c mice infected (i.v.) with P. brasiliensis) that were stimulated with hMM fractions. In the second step, female BALB/c mice were previously immunized (s.c.) with hMM fraction (25 mu g/protein = F-25 and 50 mu g/protein = F-50), and the colony-forming units (CFU) of the lung and spleen, the histopathological characteristics of the granulomatous lesions, and plasmatic gp43 soluble antigens and anti-hMM IgG levels were analyzed at 28 and 56 days after infection. The lung and liver CFU were lower in mice previously immunized with the hMM fraction (P < 0.05). The granulomatous lesions revealed a greater degree of compaction and organization, with no dissemination of the fungus to other organs. Lower soluble antigen levels (P < 0.05) and higher IgG anti-hMM fraction (P < 0.05) were observed in immunized groups. The results for CFU, histopathology and antigenemia suggest that the hMM fraction has a protective effect in experimental paracoccidioidomycosis in BALB/c mice.
Keywords: antigenemia; CFU; granuloma; Paracoccidioides brasiliensis; paracoccidioidomycosis; protection